- Tanggung Jawab Iran dalam Penggunaan Paper Satellite Zohreh-1 dan Zohreh-2 di Orbit Geostasioner Menurut Hukum Angkasa: - - Lady Dinayla Aprilyca Putri Idwani; Ayu Nrangwesti (Reformasi Hukum Trisakti, 2023)
In 1988, Iran initiated talks with Russia to launch two Zohreh telecommunications satellites at 34º and 26º positions, but this was delayed until 2003. In 2004, an updated contract was made between Iran and Russia, yet it failed to come to fruition. This research delves into the violations' nature and Iran's accountability under state responsibility. Employing normative legal research with descriptive methodology and secondary data, the study explored these questions. Literature review aided data collection, while conclusions were drawn deductively. Results revealed Iran's failure in fulfilling ITU-granted responsibilities, notably with Zohreh-1 satellite; Iran couldn't prove its launch claim. A frequency dispute emerged at the 26º BT position, housing Zohreh-2 satellite, involving Iran, France, and Arab states. ITU's resolution encompassed administrative sanctions on Iran. These issues underscore the necessity for ITU, as the authoritative Geostationary Orbit regulator, to implement more stringent measures for dispute prevention.